How Do Certified and Uncertified Therapists Differ in Their Perceptions of a Mental Health Intervention for ASD?. Issue 3 (2nd October 2017) - Dyson, Margaret W.; Chlebowski, Colby; Wright, Blanche; Brookman-Frazee, Lauren
ABSTRACT: Given the increasing efforts to implement evidence-based practices (EBPs) in routine mental health (MH) services, it is necessary to examine MH therapists' perspectives of the training and delivery process to better understand the outcomes of EBP implementation efforts and influences on these outcomes. However, there is limited research examining how therapists who successfully completed training and receive certification in an EBP intervention differ in their perceptions of these implementation outcomes and influences from those therapists who do not successfully complete training and receive certification in an intervention. As such, the present study examined variability in therapists' perspectives in the training and implementation of the An Individualized Mental Health Intervention for ASD (AIM HI) intervention, a package of well-established, evidence-based strategies developed to address challenging behaviors in children with autism spectrum disorder within community MH clinics, based on training certification status (i.e. certified vs. noncertified). Overall, both certified and noncertified therapists perceived the AIM HI intervention as useful and effective with their clients, described the increased use of structure and improved clinical skills, and reported intended sustained use of parts of the AIM HI protocol. Conversely, certified and noncertified therapists differed in their approaches to addressing the perceived challenges of EBP training and implementation, specifically time commitment and program structure, providing valuable insight into why some therapists did not achieve certification status. These data support the development of organizational leadership and provider engagement interventions designed to address attitudinal and organizational barriers to facilitate the successful training and implementation of evidence-based interventions.